A novel cash-plus intervention to safeguard sexual reproductive health and HIV vulnerabilities in young women in Cape Town, South Africa - Naledi Tracey, Noncayana (Department of Medicine, 2023)
Background Cash plus interventions augment cash transfers with other empowering interventions to influence behaviours. This research assesses the Women of Worth (WoW) program and evaluates the effectiveness of a cash transfer (CT) of ZAR300 ($22USD22) conditional on attending 12-session customised empowerment interventions to improve SRH/HIV outcomes in young women (19-24yrs) in Cape Town, South Africa. Methods A multiphase, mixed-methods, experimental study targeting 10 000 Participants in two subdistricts was conducted. Participants were randomised 1:1 to receive the interventions with CT ("cash + care" or C+C) or without CT (“Care”). Phase 1a piloted the interventions, Phase 1b implemented an adapted intervention, and Phase 2 was an open label C+C only scale up demonstration phase. Logistic regression models were fitted with subject-specific random mixed effects, to estimate changes in self-reported HIV, behavioural and structural SRH risks from baseline to (a) end of WoW and (b) follow up (6-30months post-exposure) irrespective of WoW completion. Mixed research methods were used to optimise engagement, evaluate implementation fidelity and determine the pathways of effectiveness for the interventions. Results The Women of Worth empowerment programme was implemented with adequate fidelity however adaptative research methods were essential for ensuring a sustained programme. 8765 (87,7%) of the 9995 WoW initiators were evaluated with 904 (10,3%); 4212 (48,1%) and 3649 (41,6%) women in Phases 1a, 1b and 2 respectively. In Phase 1a & 1b, participants in the “C+C” group were 60 times (OR 60.37; 95%CI: 17.32; 210.50.p